Effect of Cognitive Reserve on the Association of Vascular Brain Injury With Cognition: Analysis of the PURE and CAHHM Studies. (26th October 2021) - Durrani, Romella; Friedrich, Matthias G.; Schulze, Karleen M.; Awadalla, Philip; Balasubramanian, Kumar; Black, Sandra E.; Broet, Philippe; Busseuil, David; Desai, Dipika; Dummer, Trevor; Dick, Alexander; Hicks, Jason; et al.
Abstract : Background and Objectives: To determine whether cognitive reserve attenuates the association of vascular brain injury with cognition. Methods: Cross-sectional data were analyzed from 2 harmonized studies: the Canadian Alliance for Healthy Hearts and Healthy Minds (CAHHM) and the Prospective Urban and Rural Epidemiology (PURE) study. Markers of cognitive reserve were education, involvement in social activities, marital status, height, and leisure physical activity, which were combined into a composite score. Vascular brain injury was defined as nonlacunar brain infarcts or high white matter hyperintensity (WMH) burden on MRI. Cognition was assessed using the Montreal Cognitive Assessment Tool (MoCA) and the Digit Symbol Substitution Test (DSST). Results: There were 10, 916 participants age 35–81. Mean age was 58.8 years (range 35–81) and 55.8% were female. Education, moderate leisure physical activity, being in a marital partnership, being taller, and participating in social groups were each independently associated with higher cognition, as was the composite cognitive reserve score. Vascular brain injury was associated with lower cognition (β –0.35 [95% confidence interval [CI] –0.53 to −0.17] for MoCA and β −2.19 [95% CI −3.22 to −1.15] for DSST) but the association was not modified by the composite cognitive reserve variable (interaction p = 0.59 for MoCA and p = 0.72 for DSST). Conclusions: Both vascular brain injury and markers of cognitive reserve are associated with cognition. However, the effects were independent such that the adverse effects of covert vascular brain injury were not attenuated by higher cognitive reserve. To improve cognitive brain health, interventions to both prevent cerebrovascular disease and promote positive lifestyles are needed.